G556(P) Debrief after a Resuscitation/Death of a Child. A survey of trainee's attitudes, thoughts and experiences. (27th April 2016) - Leemon, D; Fitzsimons, A; Dalzell, E
Abstract : Context: Debrief after resuscitation may be beneficial for improving outcomes following resuscitation but can also be an opportunity to provide emotional/psychological support for the team involved. Problem: Historically in our department, debriefing happened in an ad hoc manner and it was felt that this reflected regional practice. Assessment of problem and analysis of its causes: To investigate this we developed a survey to explore the thoughts and experiences of paediatric trainees in the Northern Ireland deanery 56 out of 100 trainees replied to the survey (56%). 54% had been involved in debrief following the resuscitation/death of a child. 100% of respondents felt that debrief was beneficial and 96% would be interested in taking part in debrief as a regular occurrence. 84% of respondents felt debrief was beneficial for both clinical learning and psychological/emotional support. Of those who had been involved in debrief 18 had formal debrief, 2 had informal debrief and 10 said debrief had been both formal and informal. Regarding the preferred timing of debrief 46% felt it should occur the following day with the remainder fairly equally divided between immediately after the event or 1 week later. With regards to who should lead a debrief 80% felt that a consultant should lead with other suggestions including psychologist, senior nurse and senior trainee. 98% of respondents thought that everyone present at the resuscitation should be involved in the debrief. Intervention: Using the information obtained we plan to develop a debrief proforma/guideline to be used throughout the region. This will hopefully encourage more regular and consistent debrief following these events with the aim of achieving clinical learning and support as required. Study design: A 9 question survey was developed using Survey Monkey and a link to the survey was emailed to paediatric trainees via the Northern Ireland Medical and Dental Training Agency. The survey remained open for 4 weeks and the results were subsequently analysed. Strategy for change: We plan to develop a debrief proforma/guideline to be used throughout the region. This will hopefully encourage more regular and consistent debrief following these events with the aim of achieving clinical learning and support as required. Measurement of improvement: As well as a immediate questionaire following some pilot debrief sessions we plan to distribute a similar survey following introduction of debrief. Effects of changes: Still to be demonstrated. Lessons learnt: Only half of the repondents had experienced debrief. However most respondents felt it was beneficial and would be interested in taking part in it as a regular occurrence. Message for others: Trainees have expressed an interest in support following the resuscitation or death of a child.